Super-Treg: Toward a New Era of Adoptive Treg Therapy Enabled by Genetic Modifications - Amini, Leila; Greig, Jenny; Schmueck-Henneresse, Michael; Volk, Hans-Dieter; Bézie, Séverine; Reinke, Petra; Guillonneau, Carole; Wagner, Dimitrios L.; Anegon, Ignacio (Frontiers in Immunology, 2021)
Regulatory T (Treg) cells are essential components of peripheral immune homeostasis. Adoptive Treg cell therapy has shown efficacy in a variety of immune-mediated diseases in preclinical studies and is now moving from Phase I/IIa to larger Phase II studies aiming to demonstrate efficacy. However, hurdles such as in vivo stability and efficacy remain to be addressed. Nevertheless, preclinical models have shown that Treg cell function and specificity can be increased by pharmacological substances or gene modifications, and even that conventional T cells can be converted to Treg potentially providing new sources of Treg and facilitating Treg cell therapy. The exponential growth in genetic engineering techniques and their application to T cells coupled to a large body of knowledge on Treg open numerous opportunities to generate Treg with superpowers. This review summarizes the genetic engineering techniques available and their applications for the next-generation of Super-Treg with increased function, stability, redirected specificity and survival.